A Direct Relationship Between ‘Blood Stasis’ and Fibrinaloid Microclots in Chronic, Inflammatory, and Vascular Diseases, and Some Traditional Natural Products Approaches to Treatment - Douglas B. Kell; Etheresia Pretorius; Huihui Zhao (Pharmaceuticals)
‘Blood stasis’ (syndrome) (BSS) is a fundamental concept in Traditional Chinese Medicine (TCM), where it is known as Xue Yu (血瘀). Similar concepts exist in Traditional Korean Medicine (‘Eohyul’) and in Japanese Kampo medicine (Oketsu). Blood stasis is considered to underpin a large variety of inflammatory diseases, though an exact equivalent in Western systems medicine is yet to be described. Some time ago we discovered that blood can clot into an anomalous amyloid form, creating what we have referred to as fibrinaloid microclots. These microclots occur in a great many chronic, inflammatory diseases are comparatively resistant to fibrinolysis, and thus have the ability to block microcapillaries and hence lower oxygen transfer to tissues, with multiple pathological consequences. We here develop the idea that it is precisely the fibrinaloid microclots that relate to, and are largely mechanistically responsible for, the traditional concept of blood stasis (a term also used by Virchow). First, the diseases known to be associated with microclots are all associated with blood stasis. Secondly, by blocking red blood cell transport, fibrinaloid microclots provide a simple mechanistic explanation for the physical slowing down (‘stasis’) of blood flow. Thirdly, Chinese herbal medicine formulae proposed to treat these diseases, especially Xue Fu Zhu Yu and its derivatives, are known mechanistically to be anticoagulatory and anti-inflammatory, consistent with the idea that they are actually helping to lower the levels of fibrinaloid microclots, plausibly in part by blocking catalysis of the polymerization of fibrinogen into an amyloid form. We rehearse some of the known actions of the constituent herbs of Xue Fu Zhu Yu and specific bioactive molecules that they contain. Consequently, such herbal formulations (and some of their components), which are comparatively little known to Western science and medicine, would seem to offer the opportunity to provide novel, safe, and useful treatments for chronic inflammatory diseases that display fibrinaloid microclots, including Myalgic Encephalopathy/Chronic Fatigue Syndrome, long COVID, and even ischemic stroke.